PENGARUH TINGKAT EKONOMI ORANG TUA TERHADAP MINAT MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI PADA SISWA KELAS XII SMA NEGERI 12 SINJAI KABUPATEN SINJAI - Asnita; Kasmawati (Department of Islamic Education Management, 2023)
This study examines the influence of the economic level of parents on the interest in continuing their education to tertiary education in class XII students of SMA Negeri 12 Sinjai which aims to determine: (1) The economic level of parents on the interest in continuing their education to tertiary education in class XII students of SMA Negeri 12 Sinjai ; 2) Interest in continuing their education to tertiary education in class XII students of SMA Negeri 12 Sinjai; (3) The effect of parents' economic level on the interest in continuing their education to tertiary institutions in class XII students of SMA Negeri 12 Sinjai. This type of research uses explanatory research with the Ex Post Facto method. The population is all class XII students at SMA Negeri 12 Sinjai as many as 148 people so that a sample of 10% is drawn to 60 students using Simple Random Sampling. Data collection techniques are observation, questionnaires/questions, and documentation. The data analysis technique used is descriptive and inferential statistical analysis techniques with simple linear regression. The results of the descriptive statistical analysis show that the economic level of parents is in the medium category with a frequency of 40 people (67%) and the interest in continuing their education to tertiary education is in the high category with a frequency of 35 people (58%). The results of the inferential analysis show that the value of tcount = 0.63215 > ttable = 0.2144 means that Ha is accepted and Ho is rejected. Based on the results of these data, it can be concluded that the economic level of parents influences the interest in continuing their education to tertiary education in class XII students at SMA Negeri 12 Sinjai. The implication is to be used as literature, discourse, as well as input for parents so that their children have an interest in continuing their education to tertiary institutions to develop their potential.